2017
DOI: 10.1038/cddis.2017.506
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and functional analysis identifies galectin-1 as a novel regulatory component of the cytotoxic granule machinery

Abstract: Secretory granules released by cytotoxic T lymphocytes (CTLs) are powerful weapons against intracellular microbes and tumor cells. Despite significant progress, there is still limited information on the molecular mechanisms implicated in target-driven degranulation, effector cell survival and composition and structure of the lytic granules. Here, using a proteomic approach we identified a panel of putative cytotoxic granule proteins, including some already known granule constituents and novel proteins that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…PIBF inhibits NK cell degranulation, while recent studies revealed the ability of Gal‐1 to control the non‐secretory lytic pathway of cytotoxic cells, by influencing Fas‐Fas ligand interactions …”
Section: Discussionmentioning
confidence: 99%
“…PIBF inhibits NK cell degranulation, while recent studies revealed the ability of Gal‐1 to control the non‐secretory lytic pathway of cytotoxic cells, by influencing Fas‐Fas ligand interactions …”
Section: Discussionmentioning
confidence: 99%
“…68 In T cells, it is controlling T cell effector function homeostasis by regulating activation, differentiation, survival and cytokine production. 69 Galectin-1 is known to be a pro-tumorigenic and proangiogenic factor in cancer progression and has been associated with immune disorders such as HIV. 82 Overexpression of Galectin-1 was observed to be linked to progression of many types of cancers, including osteosarcoma, breast, lung and prostate cancers and in melanoma.…”
Section: Galectinsmentioning
confidence: 99%
“…Cancer immunotherapies targeting the interaction of human T cells with tumor cells by use of agents that bind to glycans or glycan binding proteins Many studies have aimed to induce specific immune responses against tumor-associated glycans and glycoproteins. 86 For • Induction of tolerogenic signaling and immune suppression 68,69 PRO…”
Section: Targeting the Tumor Or T Cell Glycome For Therapeutic Purposesmentioning
confidence: 99%
“…The main mechanism of cytotoxicity used by CD8+ T cells is the degranulation of granzymes and perforin, causing apoptosis in the target cells [98]. A component associated with the killing of tumor cells by CD8+ T cells is Galectin-1, which has been implicated as part of the cytotoxic granule machinery [99]. This molecule has been already described as a regulator of the CD8+ T cell expansion in vivo [100], which can eliminate antigenspecific targets in vivo [101] by acting through the Fas/FasL axis [102].…”
Section: Cancer Vaccinesmentioning
confidence: 99%